REVITALISASI TARBIYAH JASADIYAH PADA ANAK USIA DINI - ISLIYANTO (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
This study aims to elaborate the importance of tarbiyah jasadiyah in early childhood education. Given the phenomenon where children at an early age are reported to have suffered from various health problems that have been suffered by parents, such as obesity and kidney failure. With literature research and a qualitative approach, this study tries to explore various information from various literatures related to the issue of tarbiyah jasadiyah in early childhood. The results concluded that physical education in early childhood is important and affects the development of the child. In addition, physical development and health in early childhood will affect the next development in the future.